A new species of Bjerkandera (Polyporales, Basidiomycota) from Europe - Tomšovský, Michal; Sabet, Victor; Welti, Stéphane; Moreau, Pierre-Arthur; Dumez, Sylvain (Phytotaxa, 2025)
Morphological and molecular revision of pore fungi from Czechia and France revealed a new species, Bjerkandera lecomtei, sp. nov. This species is characterized by annual resupinate basidiomata, yellow ochre to deep brownish pore surface, a monomitic hyphal system with clamp connections on generative hyphae, ellipsoid to cylindrical basidiospores measuring 4.9–8.3 × 2.9–4.9 µm, and growing on hardwood (Acer campestre in floodplain forest, Quercus sp. beams, etc.). It differs from the most European Bjerkandera species by resupinate basidiome and spore sizes. Macroscopic and microscopic features and phylogenetic analyses of ITS and LSU rDNA markers are illustrated.